Caspase Exploitation by Legionella pneumophila - Krause, Kathrin; Amer, Amal O. (Frontiers in Microbiology, 2016)
Legionella pneumophila remains a major health concern, especially for hospitalized patients. L. pneumophila in the environment can survive extracellular or as protozoan parasite within amoeba. After human infection it efficiently replicates in alveolar macrophages without activating inflammasome assembly and cleavage of caspase-1. In contrast murine macrophages actively recognize intracellular L. pneumophila via inflammasome components which initiate pro-inflammatory cytokine secretion, phagosomal maturation and pyroptotic cell death thereby leading to bacterial restriction. During this process flagellin-dependent and -independent signaling pathways trigger the canonical as well as the non-canonical inflammasome. This review describes the current knowledge about L. pneumophila-induced inflammasome pathways in permissive and restrictive host cells.